Consistency of hangover experiences after a night of drinking: A controlled laboratory study. (1st December 2020) - Delang, Nathan; Iudakhina, Elizaveta; Irwin, Christopher; Desbrow, Ben
Abstract: Objective: Research into cognitive performance during a hangover has produced equivocal findings. This study investigated the reliability of inducing hangover symptoms and effects on cognitive performance (including applied tasks) under standardised conditions. Method: Twenty‐one participants (13 M; 24 ± 3 years) completed two identical trials, involving alcohol consumption and an overnight laboratory stay. Outcome measures included: hangover severity (a single‐item 'Hangover' rating, and a sum of hangover symptoms [Overall Symptoms Score (OSS)]), cognitive function (trail making test), simulated driving (standard deviation of lateral position; lane crossings), and typing performance. Spearman's correlations were used to assess reliability between trials for all participants, and when ratings of 'Hangover' were consistent. Results: Participants demonstrated reliable 'Hangover' rating change from baseline (Trial A: 2.0 [2.0]; Trial B: 2.0 [2.0], rho = 0.680, p = 0.001), but not for OSS (Trial A: 8.0 [12.0]; Trial B: 5.0 [9.0], rho = 0.309, p = 0.173). Performance in cognitive/applied tasks (range rho = 0.447–0771) was consistent, except simulated driving (range rho = 0.035–0.272), however the impairment was trivial. The subgroup analysis did not reveal substantial changes in reliability. Conclusion: A single 'Hangover' rating was a reliable way of determining 'mild' to 'moderate' hangover severity. The present data could be used to assist the methodological design of future hangover research.